1995
DOI: 10.1016/0029-7844(95)00033-n
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent molar pregnancies in a family with extensive intermarriage: Report of a family and review of the literature

Abstract: In families with extensive intermarriage and recurrent molar pregnancies, patients and their spouses may have unusual human lymphocytic antigen histocompatibility, which supports the possibility of a strong genetic predisposition expressed at the level of major histocompatibility class I and II gene translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…A careful revision of the families reported [6][7][8][9][10][11][12] suggests an autosomal recessive genotype of women experiencing recurrent familial molar pregnancies, as proposed by Helwani et al 12 Only one family has Candidate region for mole maker phenotype y been studied by molecular methods so far. 1 In this family the recurrent molar pregnancies demonstrated a biparental diploid chromosomal constitution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A careful revision of the families reported [6][7][8][9][10][11][12] suggests an autosomal recessive genotype of women experiencing recurrent familial molar pregnancies, as proposed by Helwani et al 12 Only one family has Candidate region for mole maker phenotype y been studied by molecular methods so far. 1 In this family the recurrent molar pregnancies demonstrated a biparental diploid chromosomal constitution.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Familial HM (MIM 231090) is exceedingly rare, with only seven families having been reported so far. [6][7][8][9][10][11] Consanguinity was often noted between the partners, suggesting an autosomal recessive etiology in the conceptus genotype. 10 Recently Helwani et al 12 reported a family in which consanguinity was also noted between the parents of the women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient also was a Muslim. Seoud et al (10) reported familial recurrent moles in a family with extensive intermarriage. Molar tissue should be genotyped with polymorphic DNA markers to determine the parental origin as this helps to plan therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported a new familial case of recurrent HMs occurring in three members (two sisters and their cousin) of a Lebanese family (Seoud et al 1995). Histological analysis of several molar tissues from the two sisters revealed general trophoblastic hyperplasia and the absence of fetal tissues.…”
Section: Introductionmentioning
confidence: 95%